حكم ولاية الإجبار للأب في تزويج ابنته في الشريعة الاسلامية - رشيد حسن شفاء (Al-Adab Journal, 2018)
I have chosen this subject, to be a research, called:(the rule of the mandate to force the father to marry his daughter in Islamic law). I have chosen this topic because it is important because of its spread among our societies, and the frequent forcing of women to marry against their will, and sometimes to marry them financially regardless of the husband’s religion, morals or behavior. Which led to the proliferation of family problems, and the frequent divorce between couples because of incompatibility between them My research has made this an introduction, two papers, and a conclusion. I discussed in the introduction: the reasons for choosing the topic and its importance, and the division of research. As for the first topic, it divided it into two requirements: The first requirement: the definition of the mandate of coercion, and the conditions of the guardian. The second is the order of the Patriarchs. As for the second topic: it indicates the ruling of the mandate of forcing the father to marry his daughter. The conclusion: I have shown the most important findings through research..